PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PUBLIC DEPARTEMENT BIRO PERJALANAN AN TOUR & TRAVEL - Wahyu Dwi Wicaksono; Agus Hermani (Universitas Diponegoro, 2017)
Companies engaged in the field of services is the company that every operational activities within the company depends on the human resources of the company. The management of human resources service companies are vital by reason of it can affect the performance of the company as a whole. AN Tour & Travel is one of the service company in the field of tour operator. However, due to a less good leadership and compensation that can not meet the needs of employees, employees motivation level of AN Tour & Travel are decline. The purpose of this research is to determine the influence of leadership and compensation towards employee motivation of Public Department travel agencies AN Tour & Travel employees. This research type is explanatory research. The population in this study i.e., all employees of the Public Department of 44 employees. Sampling using the saturated samples which means the number of samples are every members of the population. The measurement scale using the scale Likert. Methods of analysis used is correlation test, determination of linear regression, simple, multiple linear regression, t-test and F-test with SPSS program version 23. Based on the results of the research it is known that partially, leadership and compensation has positive effect towards the employees motivation which is indicated with the value t calculate more than t table. Significantly, variable leadership and compensation has positive effect towards employee motivation indicated by the value of F test greater than F table. Advice that can be given, namely an increase in the ability of the leadership in providing instruction and leadership capabilities in providing the working motivation for employees. In addition the diversity of types of compensation and the amount of the compensation provided to employees needs to be supplemented in order to meet all the needs of the employees.